Tobacco cessation quitlines in North America: a descriptive study - Cummins, Sharon E (BMJ Group, 2007)
BACKGROUND: Quitlines have become an integral part of tobacco control efforts in the United States and Canada. The demonstrated efficacy and the convenience of telephone based counselling have led to the fast adoption of quitlines, to the point of near universal access in North America. However, information on how these quitlines operate in actual practice is not often readily available. OBJECTIVES: This study describes quitline practice in North America and examines commonalities and differences across quitlines. It will serve as a source of reference for practitioners and researchers, with the aim of furthering service quality and promoting continued innovation. DESIGN: A self administered questionnaire survey of large, publicly funded quitlines in the United States and Canada. A total of 52 US quitlines and 10 Canadian quitlines participated. Descriptive statistics are provided regarding quitline operational structures, clinical services, quality assurance procedures, funding sources and utilisation rates. RESULTS: Clinical services for the 62 state/provincial quitlines are supplied by a total of 26 service providers. Nine providers operate multiple quitlines, creating greater consistency in operation than would otherwise be expected. Most quitlines offer services over extended hours (mean 96 hours/week) and have multiple language capabilities. Most (98%) use proactive multisession counselling—a key feature of protocols tested in previous experimental trials. Almost all quitlines have extensive training programmes (>60 hours) for counselling staff, and over 70% conduct regular evaluation of outcomes. About half of quitlines use the internet to provide cessation information. A little over a third of US quitlines distribute free cessation medications to eligible callers. The average utilisation rate of the US state quitlines in the 2004–5 fiscal year was about 1.0% across states, with a strong correlation between the funding level of the quitlines and the smokers' utilisation of them (r = 0.74, p<0.001). CONCLUSIONS: Quitlines in North America display core commonalities: they have adopted the principles of multisession proactive counselling and they conduct regular outcome evaluation. Yet variations, tested and untested, exist. Standardised reporting procedures would be of benefit to the field. Shared discussion of the rationale behind variations can inform future decision making for all North American quitlines.